Transverse polarization measurement of Λ hyperons in pNe collisions at s NN $$ \sqrt{{s}_{NN}} $$ = 68.4 GeV with the LHCb detector - The LHCb collaboration; R. Aaij; A. S. W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A. A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C. A. Aidala; et al. (Journal of High Energy Physics)
Abstract A measurement of the transverse polarization of the Λ and Λ ¯ $$ \overline{\varLambda} $$ hyperons in pNe fixed-target collisions at s NN $$ \sqrt{{\textrm{s}}_{\textrm{NN}}} $$ = 68.4 GeV is presented using data collected by the LHCb detector. The polarization is studied using the decay Λ → pπ − together with its charge conjugated process, the integrated values measured are P Λ = 0.029 ± 0.019 stat ± 0.012 syst , P Λ ¯ = 0.003 ± 0.023 stat ± 0.014 syst . $$ {\displaystyle \begin{array}{c}{P}_{\varLambda }=0.029\pm 0.019\left(\textrm{stat}\right)\pm 0.012\left(\textrm{syst}\right),\\ {}{P}_{\overline{\varLambda}}=0.003\pm 0.023\left(\textrm{stat}\right)\pm 0.014\left(\textrm{syst}\right).\end{array}} $$ Furthermore, the results are shown as a function of the Feynman x variable, transverse momentum, pseudorapidity and rapidity of the hyperons, and are compared with previous measurements.